The prevalence of non-alcoholic fatty liver disease in pediatric type 2 diabetes: a systematic review and meta-analysis - Hu, Catherine; Cioana, Milena; Saini, Amandeep; Ragganandan, Stephanie; Deng, Jiawen; Nadarajah, Ajantha; Hou, Maggie; Qiu, Yuan; Chen, Sondra Song Jie; Rivas, Angelica; Pal Toor, Parm; Banfield, Laura; et al. (Frontiers in Adolescent Medicine, 2024)
Introduction Type 2 diabetes mellitus (T2DM) is on the rise in the pediatric population. One of the main associations of T2DM is non-alcoholic fatty liver disease (NAFLD), yet the full burden of NAFLD in T2DM is unclear. This study aimed to estimate the prevalence of NAFLD and non-alcoholic steatohepatitis (NASH) in pediatric patients with T2DM. We also aimed to evaluate the association of sex, race/ethnicity, geographic location, NAFLD diagnostic methods, and glycemic control with NAFLD prevalence in this population. Methods Literature search was conducted in MEDLINE, Embase, CINAHL, the Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Reviews, and the Web of Science Core Collection from database inception to 11 May 2023. This systematic review and meta-analysis has been registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD42018091127). Observational studies with ≥10 participants reporting the prevalence of NAFLD in pediatric patients with T2DM were included. Four teams of two independent reviewers and one team with three reviewers screened articles and identified 26 papers fulfilling the eligibility criteria. Data extraction, risk of bias assessment, level of evidence assessment, and meta-analysis were performed. Results The pooled prevalence of NAFLD was 33.82% (95% CI: 24.23–44.11), and NASH prevalence was 0.28% (95% CI: 0.00–1.04). The Middle East had the highest NAFLD prevalence of 55.88% (95% CI: 45.2–66.29), and Europe had the lowest prevalence of 22.46% (95% CI: 9.33–38.97). The prevalence of NAFLD was 24.17% (95% CI, 17.26–31.81) when only liver function tests were used, but it increased to 48.85% (95% CI, 34.31–63.48) when the latter tests were combined with ultrasound. Studies reporting solely on an ultrasound-based diagnosis of NAFLD reported a prevalence of 40.61% (95% CI, 17.25–66.42) compared to 54.72% (95% CI, 34.76–73.95) in studies using magnetic resonance imaging/magnetic resonance spectroscopy. No differences in prevalence were noted based on glycemic control. Heterogeneity was high among studies. Conclusion NAFLD is a common comorbidity in pediatric T2DM. Further understanding of the optimal screening approaches for NAFLD diagnosis and evaluating its determinants and natural history are warranted to help establish its exact burden and to aid in the development of targeted screening, management, and prevention strategies for NAFLD in pediatric T2DM patients. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42018091127, PROSPERO CRD42018091127.